Adición de maíz a balanceado comercial en la crianza y pigmentación de la piel de pollos broiler (Gallus gallus) - Zambrano Paredes, Eligio Del Jesús (2015)
With the aim to assess the effects of the addition of maize to the commercial balanced on the productive indices and pigmentation of the skin of the broiler and set the profitability of treatments being studied; an investigation was conducted in the fence San Austin, parish Viche, Quininde canton. Esmeraldas Province. Located in the geographic coordinates 00 ° 36' north latitude and 79 ° 32' west longitude. The duration was 7 weeks, since 8 of january to 26 of february of 2015. The treatments are the most balanced supply of hard yellow corn in the fattening stage and end T1 5% of corn, T2 10 %, 15% T3 and T4 (0% of corn, with 4 repetitions, the experimental unit was of 10 chickens per repeat, was applied to design a complete block design (RCBD), for the comparison between the multiple range test Tukey to 95% of probability. The results show that the increased consumption of food 6036.00 g, the greater weight gain, the greater final weight 2.78 kg, the best weight to the channel 2.29 kg, it was introduced by T4 treatment (0% corn). The greater conversion of food was introduced by the T2 treatment (corn 10 % ). The best pigmentation of broiler meat 2.74 yellow was registered to use the T3 treatment (15% corn). The highest income was recorded by the T2 treatment (witness) with $213.75 dollars, with $28.67 utility which represents the benefit/coast of 1.15.